Development of breast tumour detection circuit and system using UWB pulse technology - Ong, Daniel Tian Ze. (2009)
The report documents the study of ultra-wideband (UWB) pulse technology for the development of a breast tumour detection circuit. With the increasing number of breast cancer occurrences each year, early detection becomes increasingly important and this can be realized with the use of UWB pulse technology for microwave imaging.